Analisis Kinerja Waktu dan Biaya Proyek Renovasi Kolam Renang Ranca Tales Mini Waterboom Menggunakan Metode Earned Value Management - Sudianto, Toto; Putra, Mohammad Alam Adeyaka; Fahrezi, Muhammad Akmal; Raihan, Muhammad (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study focuses on the evaluation of costs and time in the renovation project of Ranca Tales Mini Waterboom Swimming Pool by utilizing the Earned Value Management (EVM) method. The data analyzed include the planned budget, implementation schedule, work progress, and actual costs of five main components, namely pool ceramic repair, pool area painting, slide repair, pump and filter repair, and changing room repair. The analysis was carried out by measuring the BCWS, BCWP, and ACWP indicators, as well as variances and project performance indices including SV, CV, SPI, and CPI. The findings of this study show an SPI value of 0.874 which indicates a delay in the project and a CPI value of 0.945 which indicates low cost efficiency. The EVM method has proven successful in providing a quantitative overview of project performance and can be applied as a basis for managerial control and decision making.